Kemampuan Representasi Matematis Siswa Melalui Model STAD dan TPS - Agustina, Tri Budi; Sumartini, Tina Sri (Department of Mathematics Education Program IPI Garut, 2021)
Kemampuan representasi matematis siswa masih rendah. Upaya untuk meningkatkannya dengan menggunakan model STAD dengan TPS. Tujuan penelitian untuk menganalisis perbedaan kemampuan representasi matematis antara siswa yang mendapatkan model STAD dengan TPS. Metode penelitiannya yaitu kuasi eksperimen dengan populasinya adalah siswa kelas VII SMPN 2 Tarogong Kidul Garut. Pengambilan sampel dilakukan secara purposive sampling sebanyak dua kelas, yaitu kelas VII-F sebagai kelas eksperimen 1 dan VII-G sebagai kelas eksperimen 2, dengan banyaknya siswa yang lengkap mengikuti kegiatan mulai dari pretest, perlakuan, dan posttest untuk kelas eksperimen 1 sebanyak 32 siswa dan kelas eksperimen 2 sebanyak 32 siswa. Data yang dianalisis diperoleh dari hasil Pretest, Posttest, Gain Ternormalisasi dan penyebaran angket. Hasil penelitian diperoleh: 1) terdapat perbedaan kemampuan representasi matematis antara siswa yang mendapatkan model STAD dengan TPS, 2) interpretasi peningkatan kemampuan representasi matematis siswa kedua kelas berinterpretasi sedang, 3) sikap siswa kedua kelas terhadap masing-masing model pembelajaran berinterpretasi baik. Students' mathematical representation ability is still low. Efforts to improve it by using the STAD model with TPS. The purpose of the study was to analyze the differences in mathematical representation abilities between students who received the STAD and TPS models. The research method is quasi-experimental with the population being class VII students of SMPN 2 Tarogong Kidul Garut. Sampling was carried out by purposive sampling as many as two classes, namely class VII-F as experimental class 1 and VII-G as experimental class 2, with the number of complete students participating in activities ranging from pretest, treatment, and posttest for experimental class 1 as many as 32 students. and experimental class 2 as many as 32 students. The data analyzed were obtained from the results of Pretest, Posttest, Normalized Gain, and questionnaire distribution. The results obtained: 1) there are differences in the ability of mathematical representation between students who get the STAD model and TPS, 2) the interpretation of increasing the mathematical representation ability of students in both classes has a moderate interpretation, 3) the attitudes of students in both classes towards each learning model have good interpretation.